Effect of White Oyster Mushroom (Pleurotus ostreatus) Ethanol Extract on Bacillus subtilis Bacteria - Handrianto, Prasetyo; Ratnasari, Evy (Universitas Islam Lamongan, 2021)
The increasing number of infectious diseases caused by bacteria, fungi, viruses and parasites in Indonesia, and one of the bacteria that causes this disease is Bacillus subtilis. Therefore, the role of antibacterial is very important for the treatment of this disease. One of the antibacterials from nature is the white oyster mushroom (Pleurotus ostreatus). The purpose of this study was to determine the effect of various concentrations of white oyster mushroom (Pleurotus ostreatus) extract which was effective as an antibacterial against Bacillus subtilis. The research method uses the paper disc diffusion method. The results showed that the bacterial inhibition zone at a concentration of 20 g/ml obtained an average of 9.5 mm in the medium category, a concentration of 40 g/ml obtained an average of 11.3 mm in the strong category, a concentration of 60 g/ml obtained an average of 13, 3 mm in the strong category, a concentration of 80 g/ml obtained an average of 15.5 mm in the strong category and a concentration of 100 g/ml obtained an average of 17.3 mm in the strong category. The conclusion of this research is white oyster mushroom can be used as an anti-bacterial for Bacillus subtilis.